Organizational Characteristics and Social Competences: Are there differences within social competences connected with communication and co-operational skills based on the characteristics of organizations? - Zoltán Gaál; Lajos Szabó; Anikó Csepregi (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
An empirical survey aiming to investigate middle managers working at medium- and large-sized enterprises in Hungary has been conducted since 2007. Its purpose has been to reveal the competences these middle managers find important for knowledge sharing and to discover the characteristics that result in differences within the revealed competence groups. The data was analyzed using Principal Component Analysis and seven different competence groups were identified. Furthermore this research investigated whether there were differences within selected competence groups (social competencies connected with co-operational skills and communication skills) regarding the characteristics of the middle manager's organizations. As methods decision tree and analysis of variance were used. The results have shown that differences could only be found within social competences connected with co-operational skills and only regarding one of the examined organizational characteristics while no difference could be discovered within social competences connected with communication skills. By revealing the competences important for knowledge sharing, the organizations have the opportunity to develop them. Knowing which organizational features have or do not have an influence on these competence groups could help the organizations to think about methods to change it and to created and develop organizational knowledge.
Keywords: 650; competence; knowledge sharing; middle managers; organizational characteristics